Strategi Guru Pustakawan sebagai Pengelola Perpustakaan dalam Meningkatkan Kualitas Pengembangan Perpustakaan SMAN 5 Bagan Sinembah: Librarian Teacher Strategy as Library Manager in Improving the Quality of Library Development at SMAN 5 Bagan Sinembah - Rita Williana Tasya; Sayekti, Retno (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
A librarian teacher is a school teacher who has received education or training in the field of libraries for a minimum number of hours who is also assigned to the relevant school library. The position of a librarian teacher in a school library is something that cannot be avoided in the face of limited librarian staff, but it is also not a right that is taken seriously. This study aims to provide a deeper understanding of the strategy for developing school libraries managed by librarian teachers from the initial conditions that are not optimal to reaching a more efficient and effective level at the Library of SMA Negeri 5 Bagan Sinembah. The method used in this study is descriptive qualitative, with data collection techniques used in this study are interviews, observations and documentation. In the study, the strategy used by librarian teachers to improve the quality of school library development involves two main aspects: student involvement and collaboration of teaching staff, especially art and culture teachers who play a complementary role in making library facilities and infrastructure. With obstacles including limitations in library supervision due to dual responsibilities, its administration system which is still manual, and limited knowledge about digital-based library management.